THE USE OF Eucalyptus camaldulensis AND Eucalyptus urophylla WOOD IN THE PRODUCTION OF EDGE GLUED PANELS - Iwakiri, Setsuo; Trianoski, Rosilani; Stüpp, Angela; Cabral, Bruna Mulinari; Gayer, Jéssika Alvares Coppi Arruda (Floresta, 2019)
This study aimed to evaluate the shear strength of bonded wood joints of Eucalyptus camaldulensis and Eucalyptus urophylla with vinyl polyacetate (PVA) and isocianate polymeric emulsion (EPI) adhesives with the amount of glue of 150 and 180 g/m². The specimens were submitted to shear tests in dry and wet conditions, based on the procedure described in standard EN 13354 (2008). The results of the 5th lower percentile were compared with the requirements of EN 13353 (2008). Among the studied species, Eucalyptus camaldulensis showed better glue line shear strength when compared to Eucalyptus urophylla. However, both species are potentially viable for the edge glued panel (EGP) production, since they meet the minimum requirement of 2.5 MPa, referring to the 5th lower percentile, as established by EN 13353-2008 standard. Based on the results, it is recommended the use of EPI adhesive with the amount of glue of 150 g/m² for the bonding of the wood of these species, aiming at the production of EGP.